Cyclic behavior of interior RC beam-column joints strengthened with NSM-CFRP ropes. (March 2022) - Obaidat, Yasmeen Taleb
Abstract: Beam-column joints in existing concrete structures could become unsafe for many reasons, such as design error and seismic loading. Thus, in this study, the effectiveness of near surface mounted carbon reinforced polymer (NSM-CFRP) ropes for enhancing interior reinforced concrete (RC) beam-column joints was investigated. Five interior one-third scale RC beam-column joints without transverse reinforcement (stirrups) at the beam-column joints were tested under cyclic loading. The first specimen was tested as a control beam-column joint, while the four remaining beam-column joints were strengthened using NSM-CFRP ropes with a variety of CFRP rope configurations. Results were drawn based on hysteretic curves, envelope curves (load vs. drift ratio), energy dissipation, stiffness, ductility index and failure modes. The results showed that the stiffness and yield load of strengthened beam-column joints was improved compared with the control beam-column joint. The use of NSM-CFRP ropes resulted in an increase in the yield load of the strengthened beam-column joints ranging from 118.7% to 164.1% than the control beam-column joint depending on the NSM-CFRP ropes' number and its position. The use of X- shaped rope with two ropes on each side of beam and two on each side of column imparted the best effectiveness on stiffness and yield load, for instance, the stiffness increased by 236.7% compared to control beam-column joint. Finally, the bond slip occurred between the rope and concrete; therefore, the rope was only effective before the drift ratio reached 1%-1.5%, therefore, the maximum load is only affected by the RC.